Neural decoding of expressive human movement from scalp electroencephalography (EEG) - Cruz-Garza, Jesus G.; Hernandez, Zachery R.; Nepaul, Sargoon; Bradley, Karen K.; Contreras-Vidal, Jose L. (Frontiers in Human Neuroscience, 2014)
Although efforts to characterize human movement through EEG have revealed neural activities unique to limb control that can be used to infer movement kinematics, it is still unknown the extent to which EEG can be used to discern the expressive qualities that influence such movements. In this study we used EEG and inertial sensors to record brain activity and movement of five skilled and certified Laban Movement Analysis (LMA) dancers. Each dancer performed whole body functional movements of three Action types: movements devoid of expressive qualities ('Neutral'), non-expressive movements while thinking about specific expressive qualities ('Think’), and enacted expressive movements ('Do'). The expressive movement qualities that were used in the 'Think' and 'Do' actions consisted of a sequence of eight Laban Efforts as defined by LMA - a notation system and language for describing, visualizing, interpreting and documenting all varieties of human movement. We used delta band (0.2 – 4 Hz) EEG as input to a machine learning algorithm that computed locality-preserving Fisher’s discriminant analysis (LFDA) for dimensionality reduction followed by Gaussian mixture models (GMMs) to decode the type of Action. We also trained our LFDA-GMM models to classify all the possible combinations of Action Type and Laban Effort (giving a total of 17 classes). Classification accuracy rates were 59.4 ± 0.6% for Action Type and 88.2 ± 0.7% for Laban Effort Type. Ancillary analyses of the potential relations between the EEG and movement kinematics of the dancer's body, indicated that motion-related artifacts did not significantly influence our classification results. In summary, this research demonstrates that EEG has valuable information about the expressive qualities of movement. These results may have applications for advancing the understanding of the neural basis of expressive movements and for the development of neuroprosthetics to restore movements.